Principals’ Role in the Application of Reward and Punishment Systems for Promoting Student Discipline in Pesantren-Based Schools - Muhammad Holid; Fathor Rozi; Baharun, Hasan (Journal of Educational Management Research, 2025)
This study aims to examine the role of the principal in building student discipline through the reward-and-punishment approach in Islamic boarding schools. This study uses a qualitative approach of the phenomenological type, where researchers use interviews, observations and documentation. Data analysis is done through data reduction, presentation, and conclusion. The study results indicate that the principal not only carries out administrative functions but is also actively involved in students' transformative academic and character development. As an Instructional Leader, the principal fosters learning, provides supervision and builds a coaching system that integrates academics and discipline. In the role of Role Model, the principal’s exemplary attitude, discipline, and spirituality have proven effective in forming a positive culture collectively. As a Manager and Policy Maker, the principal designs a systematic reward and punishment policy based on Islamic boarding school values and is dialogical. Meanwhile, the role of a Motivator is carried out through a personal, affirmative, and inspirational approach that builds the spirit of teachers and students. The discussion results show that these four roles strengthen each other and contribute to forming an educational and sustainable disciplinary climate. This study provides implications regarding the importance of contextual, participatory, and humanistic principal leadership in managing value-based schools.